당뇨병성 족부 괴저에서 수술 전 시행한 경피적 경혈관 혈관성형술의 유용성 - 임철순; 이명진; 강정모; 조용락; 조정현; 이찬수; Im, Chul Soon; Lee, Myoung Jin; Kang, Jung Mo; Cho, Young-Rak; Jo, Jeong Hyun; Lee, Chan Soo (대한족부족관절학회지, 2018)
Purpose: Diabetic foot gangrene has a high morbidity rate and a great influence on the quality of life. Amputation is an appropriate treatment if conservative treatment is impossible according to the severity of gangrene and infection. The purpose of this study was to evaluate the usefulness of preoperative percutaneous transluminal angioplasty for the postoperative outcome. Materials and Methods: From February 2013 to April 2016, among 55 patients with diabetic foot gangrene, who require surgical treatment, percutaneous transluminal angioplasty was performed on patients with an ankle brachial index (0.9 and stenosis) 50% on angiographic computed tomography. The study subjects were 49 patients, comprised of 37 males (75.5%) and 12 females (24.5%). The mean age of the patients was $70.0{±}9.6years$. The treatment results were followed up according to the position and length of the lesion and the changes during the follow-up period. Results: As a result of angiography, there were 13 cases of atherosclerotic lesions in the proximal part, 11 cases in the distal part and 25 cases in both the proximal and distal parts. As a result of the follow-up after angiography, in 13 patients, the operation was not performed and only follow-up and dressing were performed around the wound. Sixteen patients underwent debridement for severe gangrene lesions and 20 patients, in whom the gangrene could not be treated, underwent amputation (ray amputation or metatarsal amputation, below knee amputation). Conclusion: Preoperative percutaneous angioplasty in diabetic foot gangrene patients with peripheral vascular occlusive disease is simple, and 59.2% of the patients with diabetic foot gangrene could be treated by conservative treatment or debridement.